Neuraminidase inhibitor zanamivir ameliorates collagen-induced arthritis - Sehnert, Bettina; Mietz, Juliane; Rzepka, Rita; Buchholz, Stefanie; Maul-Pavicic, Andrea; Schaffer, Sandra; Nimmerjahn, Falk; Voll, Reinhard E. (International Journal of Molecular Sciences, 2021)
Altered sialylation patterns play a role in chronic autoimmune diseases such as rheumatoid arthritis (RA). Recent studies have shown the pro-inflammatory activities of immunoglobulins (Igs) with desialylated sugar moieties. The role of neuraminidases (NEUs), enzymes which are responsible for the cleavage of terminal sialic acids (SA) from sialoglycoconjugates, is not fully understood in RA. We investigated the impact of zanamivir, an inhibitor of the influenza virus neuraminidase, and mammalian NEU2/3 on clinical outcomes in experimental arthritides studies. The severity of arthritis was monitored and IgG titers were measured by ELISA. (2,6)-linked SA was determined on IgG by ELISA and on cell surfaces by flow cytometry. Zanamivir at a dose of 100 mg/kg (zana100) significantly ameliorated collagen-induced arthritis (CIA), whereas zana-100 was ineffective in serum transfer-induced arthritis. Systemic zana-100 treatment reduced the number of splenic CD138+/TACI+ plasma cells and CD19+ B cells, which was associated with lower IgG levels and an increased sialylation status of IgG compared to controls. Our data reveal the contribution of NEU2/3 in CIA. Zanamivir down-modulated the T and B cell-dependent humoral immune response and induced an anti-inflammatory milieu by inhibiting sialic acid degradation. We suggest that neuraminidases might represent a promising therapeutic target for RA and possibly also for other antibody-mediated autoimmune diseases.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Arthritis; Mouse model; Neuraminidase; Neuraminidase inhibitor; Sialylation